2019
DOI: 10.1002/acn3.50825
|View full text |Cite
|
Sign up to set email alerts
|

1H‐31P magnetic resonance spectroscopy: effect of biotin in multiple sclerosis

Abstract: Biotin is thought to improve functional impairment in progressive multiple sclerosis (MS) by upregulating bioenergetic metabolism. We enrolled 19 patients suffering from progressive MS (5 primary and 14 secondary Progressive‐MS). Using cerebral multinuclear magnetic resonance spectroscopy (MMRS) and clinical evaluation before and after 6 months of biotin cure, we showed significant modifications of: PME/PDE, ATP, and lactate resonances; an improvement of EDSS Neuroscore. Our results are consistent with metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A previous study using DS‐removed omega plots has shown that exchange rate maps can linearly reflect the pH changes in the physiological range (pH 6.2 to 7.4) 21 . PH in MS lesions in vivo with the established 31 P‐MR spectroscopy has been consistently reported at neutral to slightly alkaline (7.03 ± 0.02) 28 . Based on our research with protein phantoms at different pH, 0.03 unit of pH will lead to k ex change of only 4 s –1 which is <1% 22 .…”
Section: Discussionmentioning
confidence: 92%
“…A previous study using DS‐removed omega plots has shown that exchange rate maps can linearly reflect the pH changes in the physiological range (pH 6.2 to 7.4) 21 . PH in MS lesions in vivo with the established 31 P‐MR spectroscopy has been consistently reported at neutral to slightly alkaline (7.03 ± 0.02) 28 . Based on our research with protein phantoms at different pH, 0.03 unit of pH will lead to k ex change of only 4 s –1 which is <1% 22 .…”
Section: Discussionmentioning
confidence: 92%
“…Both PME and PDE (slightly PDE > PME) peaks are detectable physiologically in WM and in GM (and are generally higher in WM) [ 140 , 141 ], with a gradual increase in PDE and a reduction in PME during aging, probably reflecting the cell membrane condition [ 142 , 143 , 144 ]. In the acute MS lesions of CDMS, PPMS, and SPMS patients, increased PDE concentrations (mainly attributable to the glycerophosphocholine) have been found [ 145 , 146 ], confirming higher myelin phospholipid degradation. Discrepancies have been perceived in the NAWM of MS patients, showing not only increased PDE levels in CDMS patients [ 147 ], but also decreased levels in SPMS and RRMS patients [ 137 , 148 ], supporting the hypothesis of the impact of lesion localization and of neuro-axonal tracking failure in MS patients.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Astrocytes actively participate in MS progression by means of their ability to inhibit remyelination and axonal regeneration not only by forming a glial scar, but also by supporting MS lesion formation via the production of cytotoxic factors and by contributing to mitochondrial dysfunction [ 98 , 99 , 137 ]. Therefore, an increased PME/PDE ratio is thought to provide an early indication of both demyelination and remyelination in MS patients [ 140 , 146 ].…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations